2006
DOI: 10.1103/physrevb.73.045323
|View full text |Cite
|
Sign up to set email alerts
|

Tailored quantum dots for entangled photon pair creation

Abstract: We compare the asymmetry-induced exchange splitting δ1 of the bright-exciton ground-state doublet in self-assembled (In,Ga)As/GaAs quantum dots, determined by Faraday rotation, with its homogeneous linewidth γ, obtained from the radiative decay in time-resolved photoluminescence. Post-growth thermal annealing of the dot structures leads to a considerable increase of the homogeneous linewidth, while a strong reduction of the exchange splitting is simultaneously observed. The annealing can be tailored such that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 23 publications
4
48
0
Order By: Relevance
“…15,16 On the other hand, introducing an annealing step during the growth or afterwards, their height decreases to 2 -3 nm shifting up the ground state energy well above 1.3 eV. 17 Therefore, we conclude that the height values found for type-A and type-B QDs are compatible with the fundamental transitions observed in their PL spectra.…”
supporting
confidence: 67%
“…15,16 On the other hand, introducing an annealing step during the growth or afterwards, their height decreases to 2 -3 nm shifting up the ground state energy well above 1.3 eV. 17 Therefore, we conclude that the height values found for type-A and type-B QDs are compatible with the fundamental transitions observed in their PL spectra.…”
supporting
confidence: 67%
“…We have observed that the anisotropic splitting con-tinuously decreases with the interband energy emission of the QDs. Similar trends have already been observed in thermally annealed samples [4][5][6][7], and have been interpreted as a symmetrizing of the inplane e-h confinement potential induced by the In diffusion. The anisotropic splitting is a fundamental property of interest: for instance, its cancellation would allow the creation of entangled photon pairs with QDs [8].…”
Section: Introductionsupporting
confidence: 82%
“…Control of the dot dimensions allows tuning of the electronic structure of the dot, and thus the emission energies and level spacings [49]. This is of particular relevance to entangled photon pair generation [50][51][52][53], where the dot size and shape will determine whether the photon polarizations are entangled, or simply correlated [47].…”
Section: Directed Self-assemblymentioning
confidence: 99%
“…In anisotropic quantum dots the electron-hole exchange interaction splits the two excitonic states by ¡ AES (see in the ¡ AES through the application of external magnetic [70] and electric [43,44] fields, or through spectral filtering [71], applied uniaxial stress [72], and quantum size and composition engineering [50][51][52][53]. An alternative scheme [73,74] involves manipulation of the biexciton binding energy.…”
Section: Non-classical Light Sourcesmentioning
confidence: 99%